2001
DOI: 10.1095/biolreprod64.5.1451
|View full text |Cite
|
Sign up to set email alerts
|

Outer Dense Fiber Proteins Are Dominant Postobstruction Autoantigens in Adult Lewis Rats1

Abstract: Obstruction of the male reproductive tract commonly results in generation of antisperm autoantibodies. However, only a few of the sperm autoantigens recognized by these antibodies have been characterized. To identify postobstruction rat sperm autoantigens, sperm proteins were separated by two-dimensional(2-D) gel electrophoresis. Spots corresponding to proteins that were stained by at least 50% of postvasectomy rat sera on 2-D Western blots were removed from polyacrylamide gels and microsequenced by tandem mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 58 publications
1
17
0
Order By: Relevance
“…A Coomassie-stained gel band was processed by standard procedures. 28 In short, CDK2 was reduced, alkylated and digested with trypsin in-gel to produce peptides suitable for sequencing by mass spectrometry. Sequencing was accomplished using a ThermoElectron LTQFT mass spectrometer.…”
Section: Methodsmentioning
confidence: 99%
“…A Coomassie-stained gel band was processed by standard procedures. 28 In short, CDK2 was reduced, alkylated and digested with trypsin in-gel to produce peptides suitable for sequencing by mass spectrometry. Sequencing was accomplished using a ThermoElectron LTQFT mass spectrometer.…”
Section: Methodsmentioning
confidence: 99%
“…These results indicate that Sptrx-3 is a post-obstruction sperm autoantigen, at least in some animals. Because vasectomy mimics immunization of rats with spermatozoa (46), the postvasectomy sera reacted with multiple other protein spots (39,45). Study of a limited set of postvasectomy sera showed that two sera stained spots that comigrated with those bound by anti-SPTRX-3 serum (Fig.…”
Section: Fig 4 Expression Pattern Of Sptrx-3 Protein In Human Testismentioning
confidence: 99%
“…For 2-D sodium dodecyl sulfate-polyacrylamide gel electrophoresis (2-D SDS-PAGE) of rat epididymal fluid proteins and sperm extracts, isoelectric focusing (IEF) in the first dimension was performed using gel and ampholine (isoelectric point [pI] of 3.5-6.5) compositions described previously [17]. Sperm extracts containing 150-200 g of protein or 200-250 g of solubilized epididymal fluid proteins were separated on 2-D (IEF and SDS-PAGE) gels and transferred to nitrocellulose paper [29].…”
Section: Two-dimensional Electrophoresismentioning
confidence: 99%
“…The resulting postobstruction sera and hyperimmune sera reacted on 1-D or 2-D Western blots with subsets of sperm proteins, which were thereby identified as autoantigens, isoantigens, or both [16]. Microsequencing analysis subsequently revealed the outer dense fiber proteins odf1 and odf2 [17], sperm mitochondria-associated cysteine-rich protein (SMCP) [18], and the testis-abundant protein termed asparaginase-like protein (ALP) [19] as major rat sperm autoantigens. Less attention has been given to the antigenicity of epididymal proteins, although the abundant epididymal protein DE has been characterized as an isoantigen and an autoantigen in rats [20].…”
Section: Introductionmentioning
confidence: 99%